2018
DOI: 10.1155/2018/5209494
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Properties of Clean Sand Modified with Granulated Rubber

Abstract: Waste automobile tires are used as additives or replacements instead of traditional materials in civil engineering works. In geotechnical engineering, tires are shredded to certain sizes and mixed with soil, especially used as backfill material behind retaining walls or fill material for roadway embankments. Compared to soil, rubber has high damping capacity and low shear modulus. Therefore, it requires the determination of the dynamic characteristics of rubber/soil mixtures. In this paper, the cyclic behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Sarajpoor et al [ 7 ] reported that at shear strain amplitudes less than about 0.1%, an increase in rubber volume content results in a higher damping ratio, while at shear strain amplitudes greater than about 0.1%, the opposite trend is observed. While Senetakis et al [ 21 ] showed similar conclusions, it should be noted that Okur et al [ 29 ] obtained contrary findings using resonant column tests, indicating that under shear strain amplitudes less than about 5 × 10 −2 %, an increase in rubber volume content leads to a lower damping ratio, with the reverse being true under greater shear strains. Madhusudhan et al [ 30 ] even reported that the damping ratios of sand–rubber mixtures decrease with increasing shear strain range.…”
Section: Introductionmentioning
confidence: 93%
“…Sarajpoor et al [ 7 ] reported that at shear strain amplitudes less than about 0.1%, an increase in rubber volume content results in a higher damping ratio, while at shear strain amplitudes greater than about 0.1%, the opposite trend is observed. While Senetakis et al [ 21 ] showed similar conclusions, it should be noted that Okur et al [ 29 ] obtained contrary findings using resonant column tests, indicating that under shear strain amplitudes less than about 5 × 10 −2 %, an increase in rubber volume content leads to a lower damping ratio, with the reverse being true under greater shear strains. Madhusudhan et al [ 30 ] even reported that the damping ratios of sand–rubber mixtures decrease with increasing shear strain range.…”
Section: Introductionmentioning
confidence: 93%
“…As stated earlier, the main objective of this study is to obtain hysteresis loops for soil samples, using data recorded by accelerometers inside the soil in the shaking table tests, and then, to use these loops to determine the changes in the shear modulus and the damping ratio versus shear strain in the fixed number of cycles (for comparison, the total number of cycles is identical at all frequencies). Similar studies have already been carried out by researchers using the aforementioned concepts to determine the rubber content effects and various parameters on the dynamic properties of soils, especially sand (e.g., Okur and Umut, 2018;Senetakis et al, 2012;Anastasiadis et al, 2012;Koga and Matsuo, 1990;Abdel-Ghaffar and Sčoty, 1979;Kikusawa and Hasegawa, 1985;Ghayamghamian and Kawakami, 2000;Bahadori and Manafi, 2015).…”
Section: Hysteresis Stress-strain Relationship and Dynamic Propertiesmentioning
confidence: 77%
“…e main tests used include dynamic triaxial test, resonant column test, and cyclic simple shear test. By summarizing the test results, the following conclusions can be drawn: the dynamic shear modulus of rubber sand decreases with the increase of rubber content, the dynamic elastic modulus decreases with the increase of tire particle content, the equivalent damping ratio increases first and then decreases with the rubber particle content, and the dynamic characteristics of rubber sand are greatly affected by water content, and the influence of particle size can be ignored [81][82][83]. In this regard, rubber sand with 20% rubber particle content can be selected in engineering projects [84].…”
Section: Mechanical Properties Of Rubber Modified Sandmentioning
confidence: 98%